2015
DOI: 10.1590/1677-3225v14n3a10
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse: perception and knowledge by Public Health Dentistry teams in Brazil

Abstract: Aim: To evaluate the experience, knowledge and attitudes of dentists and oral health technicians (OHTs) who work in Basic Health Units in the city of Curitiba, PR, Brazil, regarding cases of abuse against children and adolescents. Methods: In this observational study, three hundred eighty-three questionnaires (validated for Brazilian Portuguese) were sent to dentists and OHTs who work in public health units. The response rate was 38.12% (n = 146) for dentists and 40% (n = 77) for OHTs. Results: The mean age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
1
12
0
6
Order By: Relevance
“…Suspecting child abuse and its reporting are problematic areas in dentistry. Dalledone et al . reported a significant correlation between suspecting child abuse and the duration of experience in the profession.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suspecting child abuse and its reporting are problematic areas in dentistry. Dalledone et al . reported a significant correlation between suspecting child abuse and the duration of experience in the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for not reporting suspected cases of child physical abuse, include ‘uncertainty about the diagnosis’, which was the most common reason cited in many studies. ‘Not knowing the role of the dentist in reporting’, ‘lack of information’ and ‘confidentiality concerns’ were the other reasons. In this study, the lack of information on where to report and documents for reporting were the two main reasons for not reporting suspected cases of child physical abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Only 11.4% of the dentists knew the procedure. Dalledone et al (35) stated that 35.67% of the dentists reported suspected cases to authorities in Brazil. There are many studies from all over the world which reported similar findings (17,(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…[21] International studies have shown that dental health personnel do suspect child maltreatment among their patients. [22][23][24][25][26][27][28][29][30] However, detecting child maltreatment can be difficult, and in relation to oral health, it is hard to determine common features that characterize dental neglect. [18] Dental health personnel find their duty to report challenging and do often fail to report their suspicions to CWS.…”
Section: Introductionmentioning
confidence: 99%
“…This disparity is in accordance with other studies. [22][23][24][25][26][27][28][29][30][31] The challenges dental health personnel experience when suspecting child maltreatment and deciding whether to report to CWS may be related to difficulties making decisions under uncertainty. [32] More specifically, signs of child maltreatment are often unclear and ambiguous and the consequences of reporting to CWS are often unclear.…”
Section: Introductionmentioning
confidence: 99%